Asymmetric monetary policy rules for the euro area and the US - Maih, Junior,Mazelis, Falk,Motto, Roberto,Ristiniemi, Annukka (Norges Bank, 2021)
We analyse the implications of asymmetric monetary policy rules by estimating Markovswitching DSGE models for the euro area (EA) and the US. The estimations show that until mid-2014 the ECB's response to inflation was more forceful when inflation was above 2% than below 2%. Since then, the ECB's policy can be characterised as symmetric, and we quantify the macroeconomic implications of this policy change. We uncover asymmetries also in the Fed's policy, which has responded more strongly in times of crisis. We compute an optimal simple rule for the EA and the US in an environment with the effective lower bound and a low neutral real rate, and find that it prescribes a stronger response to inflation and the output gap when inflation is below target compared to when it is above target. We document its stabilisation properties had this optimal rule been implemented over the last two decades.
11250/2783870
Keywords: Graue Literatur; Inflation targeting; Markov-switching DSGE; optimal monetary policy; effective lower bound; Bayesian Estimation